Strength performance of coconut fiber ash as cementitious material - Zarith Dahlia, Mohamed Zameri (2014)
Natural fiber ash is the product that is produce from the burning process of the specific type of natural fiber that exist in this world for example sisal fiber, jute fiber, kenaf fiber, and bamboo fiber. For more specific, natural fiber is actually the thread like materials which can be used for different purposes and also can be used in different application of field. Other than that, the other benefits of natural fiber are can lead to have sustainable development , easy usage/handling of fibers due to their flexibility, have good strength- and stiffness-to-weight ratios, and require only around 20-40% of the production energy. By using the natural fiber ash in concrete production, we can minimize the amount of cement used and definitely it can save the cost of construction due to the expensive cost of cement. In this study, the coconut fiber ash will be used as cementitious material in order to produce high strength concrete and will be burn in furnace for 2 hours at 5000C. Not only that, the concrete with cementitious materials can be stronger and have high durability than concrete with Ordinary Portland cement (OPC). The percent replacement of the ash used are 1%, 2%, 3% and 4% from the weight of cement used and will be compared with 0% (without coconut fiber ash replacement). The testing that will be conduct in this study is fixed for all size cubes (100 x 100 x 100 mm) that are compressive strength. The curing days are 7 days, 14 days and 28 days. From the data during this study was conduct, the most successful compressive strength is the concrete with 1% coconut fiber ash replacement than the others percentage.